Evaluation of biological changes at the proximal contacts between single-tooth implant-supported prosthesis and the adjacent natural teeth - An in vivo study - Maria Roseme Kandathilparambil; Vizaikumar Vasudha Nelluri; Bhanu Chander Vayadadi; Naveen Kumar Gajjam (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim of the study is to evaluate the proximal contact tightness (PCT) between single-tooth implant-supported prosthesis (ISP) and the adjacent natural teeth with and without the intervention of the Essix retainer at the end of 1 year. Settings and Design: In vivo -experimental study. Materials and Methods: Forty patients with a single ISP in the first molar region of the mandibular arch are included in the study who were randomly divided into two groups - Group I (20): those without an intervention of Essix retainer and Group II (20): those with the intervention of Essix retainer (2 mm thickness) (Thermo Vac, Inc. USA) delivered immediately after the restoration of implant with the definitive prosthesis. The groups are further subdivided into Subgroups A (control) and B within Group I and Subgroups C (control) and D within Group II. Mesial and distal PCT values were recorded in each quadrant using the digital force gauge, and values obtained at the end of 1 year were subjected for statistical analysis. Statistical Analysis Used: Independent sample t-test was performed. P < 0.05 was taken as statistically significant. Results: On nonusage of Essix retainer, in comparison to the control group, there were a 57.9% decrease in PCT values for the ISP on mesial contact (P < 0.05) and a 38.9% decrease for the distal contact (P > 0.05), whereas on the usage of Essix retainer, the PCT values for ISP on mesial contact decreased to 25.3% (not significant) and 33.7% on the distal contact (P > 0.05). The incidence of contact loss was found to be 30%, whereas it decreased to 15% on the usage of Essix retainer. Conclusion: The usage of Essix retainer showed a significant difference in increasing the PCT values, especially on the mesial contact. The incidence of contact loss, which was found to be 30%, decreased to 15% on its usage.